Validation of molecular markers for wheat resistance to Fusarium head blight in Brazilian wheat genotypes - Scherloski, Adriana; Montecelli, Tatiane Dalla Nora; Mioranza, Franciele; Lazzari, Fabiane; Polo, Leandra Regina Texeira; Schuster, Ivan (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to validate 19 microsatellite markers for wheat resistance to Fusarium head blight (FHB), in an unstructured population. Molecular markers described in the literature as flanking QTLs of FHB resistance in wheat on chromosomes 3B, 5A, and 6B were used. Ninety six wheat lines and cultivars were evaluated for severity of FHB infection in two evaluation years. The lines and cultivars were genotyped with 19 microsatellite markers. The obtained data were analyzed by Tukey’s test, and by correlation, simple linear regression, and multiple regression analyses; the efficiency of selection with molecular markers was also estimated. Disease severity ranged from 1.95 to 41.3% in the mean of the two years. QTLs in the three evaluated chromosomes were validated. The markers Xgwm389, Xgwm533, Xbarc180, Xbarc24, Wmc397, Xbarc101, and Wmc398 were significantly associated with FHB resistance in wheat, and alleles for susceptibility and resistance were identified. The markers Wmc397, Xbarc101 (chromosome 6B), and Xbarc180 (chromosome 5A) have potential for use in marker‑assisted selection for resistance to FHB in wheat.